I need to see the diagram in order to answer your question.
Answer:
Firstly, rewrite the equation:
⅓ (18 + 27) = 81
Substitute x for the given number of it's supposed equivalent.
In this case x = 12.
⅓ (18(12) + 27) = 81
Solve using PEMDAS and simplify what is in the parenthesis first. Then, multiply.
(18 x 12) + 27 = 243
Now, solving using PEMDAS, multiply the total of what you got that was originally in the parenthesis by ⅓ .
⅓ (243) = 81
When you multiple these number they are equivalent to 81.
81 = 81
Since the equation given, when substituted x for 12, is equivalent to 81, this proves that substituting x for 12 makes this equation true.
Answer:
x = -2, y=1
Step-by-step explanation:
x-7y=-9---------------------equation 1
-x+8y=10-------------------equation 2
From equation 1, make x the subject of formula
x=7y-9----------------------equation 3
substituting x=7y-9 in equation 2,
-(7y-9)+8y=10
Expanding bracket
-7y+9+8y=10
Collecting like terms
8y-7y=10-9
y=1
substituting y=1 in 3
x=7(1)-9
x=7-9
x=-2
Answer:
Step-by-step explanation:
1.159 R (remainder) 42
| ------------------------
73 | 84.649
-73
116 (brought 6 down)
-73
434 (brought 4 down)
-365
699 (brought 9 down)
-657
42 is the remainder
173888888888888888888888888888